The use of innovative technologies in mathematics teaching it is also a means of correction in special school - Dilobar Botirovna Yakubjanova (Proceedings of The ICECRS, 2020)
This paper analyses the use of innovative technologies in mathematics teaching it is also a means of correction in special school. On this case , research has been pointed on theoretical and methodological views. Finally, research has been concluded with outcomes and shortcomings as the whole.